Godsdiensvryheid en Formele Onderwys: ’n Reformatories Histories-opvoedkundige Ondersoek - van NIekerk, E. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2005)
The article firstly examines the historical developments related to religious education in Afrikaner education from 1652 - 2004. This is largely done utilizing education laws relating to this subject in the following periods: the first Dutch occupation, the period in the Zuid-Afrikaansche Republiek before the Anglo Boer War, the period when the Transvaal Colony was in existence, the period during which Christian National Education was in vogue and, lastly, the post 1994 era. Secondly the historical developments in Afrikaner religious education are then related to trends in Western cultural development from the Renaissance. Against this historical background religious freedom in education is then discussed from a reformational Christian perspective.